Organo-refining of high-ash Indian coals at bench scale. (1st February 2016) - Chandaliya, V.K.; Biswas, P.P.; Dash, P.S.
Graphical abstract: This process has been demonstrated at bench scale. Organic matters were extracted from the coal using organic solvents. Clean coal with <10% ash was produced from feed having 30% to 40% mineral matter. Highlights: Production of <10% ash clean coal from 30% to 40% feed ash coal at bench scale. 6–12% points moisture reduction by decanter centrifuge over basket centrifuge. Mixing of two raw coals give 6% more yield rather than mixing their extracts. Free Swelling Index (FSI) improved from 1–5 range for feed coal to 7–8 for products. Abstract: Organo-refining is a process of solvent extraction through which organic matters are extracted from coal using organic solvents. Indian coals have high mineral matter content ranging from 25 to 45 wt.% (dry basis). The ash in coal is highly disseminated, which makes it difficult to remove by physical beneficiation. Thus, chemical beneficiation is needed to remove the mineral matter. This study was conducted for high ash Indian coals at bench scale. The capacity of the bench scale plant was 40 kg/batch feed basis. Coking coal, washery discards and thermal coals of bituminous origin were used as feed material. The mineral matter of these coals varied in the range of 27–36 wt.% (db). The feed size of the particle was below −0.5 mm. N-methyl-2-pyrrolidone (NMP) and ethylenediamine (EDA) were used as main solvent and co-solvent respectively. The extraction was done at 200 °C with 1:6 coal to solvent ratio (by mass, wt./wt.) for 60 min. Extraction was followed by solid–liquid separation, solvent recovery and washing of products. The feed and product materials were subjected to proximate analysis, ultimate analysis, and Free Swelling Index (FSI) tests. Organo-refining process produced clean coal yield in the range of 30–45% and clean coal mineral matter was less than 10% for coking as well as non-coking coals. Free Swelling Index (FSI) also improved from 1–5 range for feed coals to 7–8 for product clean coals. Two types of filter (basket and centrifuge) were also tried for separation of solid and liquid from different types of slurries. It was observed that cake moisture can be reduced by 6–12% points for these slurries using decanter centrifuge. The cake moisture reduced to 70% from 76% for clean coal slurry and 60% to 48% for reject slurry. The clean coal yield increased by 5 units (from 35% to 40%) with decanter centrifuge filter. In order to have better filtration and precipitation, the extraction was carried out by mixing of two different raw coals (TL and TC) in a certain ratio (1:1 to 1:3). Also, the extraction was done separately for TL and TC coals and then the clean coal extracts were mixed in 1:1 to 1:3 proportions. Mixing of two raw coals gives better results (36 wt.% yield with 6.4% ash clean coal) than mixing of their extracts (30 wt.% yield with 6.7% ash clean coal).